Mengoptimalkan Tugas Pokok Perawat Gigi di Puskesmas (Kajian Tinjauan Pustaka) - I Made Budi Artawa; Ni Nyoman Dewi Supariani; I Nyoman Wirata; Anak Agung Gede Agung; I G A Raiyanti (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2020)
The main duty of the dental nurse at health center are planning, preparing and doing service of tooth and mouth healthy in individual, group, and society in healthy facility include at health center. Looked on the important of service target achievement of dental and mouth healthy, so the main duty of the dental nurse must be optimal. This unsuccessful show by the national survey result riskedas Bali, that is low number of tooth defence that only reach 42,4 %, resident that have care by medical only 1,7 %. Konseling care/ clean of the tooth only 12,7 %. Besides resident’s behavior on caring of the tooth and mouth cleaness is in low number that show by the percentage of the residents that in 10 years old which brushes teeth everyday are 82,2 %, but that brushes their teeth with the right way and time only 16%. Low number of optimalization when do the main duty dental nurse caused by un knowledge the dental nurse of their main duty. Dental nurse, know about their main duty but not do it, and there are no straightening of the regulation. The way to optimalize main duty of dental nurse in the health center are motivate for the next study and serve exercise of dental and mouth healthy to the dental nurse that passed the SPRG, make a rule about do the main duty in the health center, assesmant functional credits number of the dental nurse must be fixed, and doing a meeting between the of PPGI, of PDGI, school institution, health center and Dinkes for talk about the realization of dental nurse’s main duty and rebuild the format ricord of dental care service in health center. Optimal of the main duty of dental nurse will support the reach of Millennium Dielopment Goals (MDG’s)